3D-printed thermally expanded monolithic foam for solid-phase extraction of multiple trace metals - Cheng, Yu-Hsuan; Su, Cheng-Kuan (Mikrochimica acta (1966), 2024)
Digital light processing (DLP) 3DP, commercial acrylate-based photocurable resins, and thermally expandable microspheres-incorporated flexible photocurable resins were employed to fabricate an SPE column with a thermally expanded monolithic foam for extracting Mn, Co, Ni, Cu, Zn, Cd, and Pb ions prior to the determination using inductively coupled plasma mass spectrometry. After optimization of the thermally activated foaming, the design and fabrication of the SPE column, and the automatic analytical system, the DLP 3D-printed SPE column with the thermally expanded monolithic foam extracted the metal ions with up to 14.8-fold enhancement (relative to that without incorporating the microspheres), with absolute extraction efficiencies all higher than 95.6%, and method detection limits in the range from 0.5 to 5.2 ng L –1 . We validated the reliability and applicability of this method by determination of the metal ions in several reference materials (CASS-4, SLRS-5, 1643f, and Seronorm Trace Elements Urine L-2) and spiked seawater, river water, ground water, and human urine samples. The results illustrated that to incorporate the thermally expandable microspheres into the photocurable resins with a post-printing heating treatment enabled the DLP 3D-printed thermally expanded monolithic foam to substantially improve the extraction of the metal ions, thereby extending the applicability of SPE devices fabricated by vat photopolymerization 3DP techniques. Graphical abstract